2007
DOI: 10.1111/j.1445-2197.2007.04055.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome of Superficial and Deep Castleman Disease

Abstract: Whether Castleman disease is superficial or deep has no effect on surgical outcome as long as resection is complete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 33 publications
0
37
0
1
Order By: Relevance
“…According to the latest investigations, complete resections provide the same surgical results in deep and superficial CD (29). No recurrences have been reported in the literature after complete resection of the hyaline vascular type.…”
Section: Discussionmentioning
confidence: 83%
“…According to the latest investigations, complete resections provide the same surgical results in deep and superficial CD (29). No recurrences have been reported in the literature after complete resection of the hyaline vascular type.…”
Section: Discussionmentioning
confidence: 83%
“…Surgical excision appears to be the ideal treatment approach for UCD in five other small retrospective studies [14][15][16][17][18]. In total 55 patients with UCD were reviewed, all were treated with surgery (open thoracic surgery or VATS).…”
Section: Resultsmentioning
confidence: 99%
“…Schulte et al 16 reported that if possible oncological resection must be performed for disseminated CD. When complete resection is impossible, palliative resection or radiotherapy may be used to control possible systemic manifestations 4,9 . A systemic therapy including chemotherapy, steroid and antiviral therapy should be given to the patients with symptomatic multicentric CD.…”
Section: Discussionmentioning
confidence: 99%
“…Flendrig and Schillings 2 described two distinct pathologic types and one mixed variant, while Keller et al 3 reported hyaline-vascular, plasma cell and hyaline-vascular plasma cell type. Little is known about the cause of this disease, which may occur anywhere along the lymphatic chain, but it is most commonly located in the mediastinum 4 . It usually presents as a localized soft tissue mass in the neck or the mediastinum; however, it has also been reported that the mesentery, pelvis, pancreas, adrenal and retroperitoneum may also be included in other extrathoracic involvement [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation